(untitled) (Economic and Political Thought, 2016)
Taking into account wider autonomous competences at the European level and the appreciation of the information phenomenon – the need for a redefinition of the role, function and place of intelligence is outlined (not only in the structure of the state but also in the global transnational alliances). Europe needs a common sense of security, unified threat perception, and thus joint risk assessments. For this reason, the EU must provide a framework for intensifying cooperation, at least by developing intelligence community – matched with declared political ambitions of Europe. The question is whether the EU needs specially dedicated intelligence agencies in this regard, or if intuitions operating at the level of the EU and the Member States are sufficient. And if so, which agencies – and how constructed and communitarised. If the European Common Intelligence Policy cannot be treated in institutional terms, it is only because of the lack of political will. Obstacles are among others: lack of trust, finances, loss of foreign partners, technical and logistical issues, legal and institutional aspects, cultural differences, politics and ideology. In the case of a change of political will, and preparing proposals for solutions, one can talk about the extension of the current model retaining the status quo or an increased cooperation model, or a model of full European intelligence with the European Intelligence Agency at the helm.